2013
DOI: 10.2478/bvip-2013-0042
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Cortisol Levels in Horses and their Riders During Three-Day-Events

Abstract: The group of 36 warm-blooded half-bred horses (18 stallions and 18 mares) and their riders (20 men and 16 women), who ended three-day-events, were selected for the study. The horses were aged 4 to 6 years, while the riders were 19 to 34-year-old. The saliva samples were collected after each phase of the competitions. The cortisol concentration was determined using an immunoassay method. The following factors were considered: type of competition, horse sex, and rider gender. In horses, the statistically importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 19 publications
3
14
2
Order By: Relevance
“…This observation is not consistent with the results of other studies, in which males showed greater cortisol response to stress than females [12]. Similar results to Franco et al [12] were shown by Strzelec et al [13], where females Averages with different letters (a, b in columns, x, y in rows) differ significantly at P ≤ 0.05. Averages with different letters (a, b in columns, x, y in rows) differ significantly at P ≤ 0.05. participating in eventing had significantly lower level of cortisol concentration than males.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…This observation is not consistent with the results of other studies, in which males showed greater cortisol response to stress than females [12]. Similar results to Franco et al [12] were shown by Strzelec et al [13], where females Averages with different letters (a, b in columns, x, y in rows) differ significantly at P ≤ 0.05. Averages with different letters (a, b in columns, x, y in rows) differ significantly at P ≤ 0.05. participating in eventing had significantly lower level of cortisol concentration than males.…”
Section: Discussioncontrasting
confidence: 65%
“…Significant differences were not found between cortisol concentrations before exercise in both age groups of riders. Higher level of older juniors can be influenced by the atmosphere of rivalry before competition as well as after jumping round because of a bigger emotional engagement of more experienced athletes [13].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies confirm the high correlation between the stress response and HR (8,9,15). This was also proven in a study where HR values were correlated together with the level of cortisol -the stress hormone (5,19,23). Therefore, on the basis of the obtained results, it is possible to correlate HR with reactions on particular behavioural interactions between horses and humans, environment and breeding procedures.…”
Section: Discussionsupporting
confidence: 49%
“…A nervous mood can be transmitted from humans to horses under handling and riding conditions [9]. Voice [10][11][12], posture [13,14], facial expression [15,16], autonomic signals [17][18][19], hormones [20][21][22][23] and pheromones [24] might be used to fruitfully describe and characterize the emotional content [25]. Non-verbal communication between human and horse was also investigated in [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in [39], the link between horse and human was also investigated by studying their electroencephalograph signals (EEG), revealing a higher synchronicity in EEG waves at increasing interactions. A correlation analysis between human and equine hormone concentrations was performed in [20,21].…”
Section: Introductionmentioning
confidence: 99%